Political Motive in Terrorism Criminal Act - ., Sudarsono (2017)
Motives that form the background of terrorism criminal act can be anything, and one of them is political factor. Hence, there must be a concrete and clear explanation upon terrorism criminal act in order to define whether a crime is classified as terrorism or usual crime. Petrus Golose elaborates some reasons that may cause terrorism movement, namely Nation-Separatism, an act which has objective to get independence; Ethnocentrism, an act which is driven by specialty upon social degree and race; Revolution, an act which has motivation to coup d’etat; Religious motive, an act which is based on fundamental belief; Ideology, an act which means a belief upon special political mainstream; and Mental disorder, an act which is conducted due agent’s mental disorder[1]. Again, terrorism is not merely a matter of law disobedience or law enforcement; terrorism criminal acts that happen, as a matter of fact, can be assured their ideological backgrounds and there must be hidden interests of power. In short, the factors that cause terrorism are manifold. In order to portrait the phenomena of violence and to formulate regulation upon terrorism criminal crime, as consequence, cannot rely on one approach. Analysis upon terrorism criminal act anticipation, therefore, must be based on some views and also on the motives that form the background. Keywords: Terrorism, Criminal Act, Motive [1] Golose, Petrus Reinhard. 2009. Deradikalisasi Terorisme: Humanis, Soul Approch dan menyentuh Akar Rumput, YPKIK, Jakarta